Isolation of skeletal muscle stem cells by fluorescence-activated cell sorting - Liu, Ling; Cheung, Tom H; Charville, Gregory W; Rando, Thomas A (Nature protocols, 2015)
In this protocol, limb muscles are physically and enzymatically dissociated to maximally release resident mononucleated cells. Pure populations of either quiescent or activated muscle stem cells are then isolated by flow cytometry. The prospective isolation of purified stem cell populations has dramatically altered the field of stem cell biology, and it has been a major focus of research across tissues in different organisms. Muscle stem cells (MuSCs) are now among the most intensely studied stem cell populations in mammalian systems, and the prospective isolation of these cells has allowed cellular and molecular characterizations that were not dreamed of a decade ago. In this protocol, we describe how to isolate MuSCs from limb muscles of adult mice by fluorescence-activated cell sorting (FACS). We provide a detailed description of the physical and enzymatic dissociation of mononucleated cells from limb muscles, a procedure that is essential in order to maximize cell yield. We also describe a FACS-based method that is used subsequently to obtain highly pure populations of either quiescent or activated MuSCs (VCAM + CD31 − CD45 − Sca1 − ). The isolation process takes ∼5–6 h to complete. The protocol also allows for the isolation of endothelial cells, hematopoietic cells and mesenchymal stem cells from muscle tissue.